Biological Analyses for Characterization of the Uterine Sarcoma Using Mouse Model - Takuma Hayashi; Tomoyuki Ichimura; Mari Kasai; Yae Kanai; Hirofumi Ando; Koichi Ida; Nobuo Yaegashi; Susumu Tonegawa; Ikuo Konishi (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Uterine sarcomas are neoplastic malignancies that typically arise in tissues of a mesenchymal origin in uterine body. The identifi cation of novel molecular mechanisms leading to sarcoma formation, and the establishment of new therapies and biomarkers has been hampered by several critical factors. Uterine leiomyosarcoma (U-LMS), which is the most common sarcoma, is rarely observed in clinical settings, with fewer than 15,000 new cases being diagnosed each year in the United States. Another complicating factor is that U-LMS are extremely heterogeneous as they arise in a multitude of tissues from many different cell lineages. The scarcity of clinical samples coupled with its inherent heterogeneity creates a challenging experimental environment for clinicians and scientists. Faced with these challenges, there have been extremely limited advances in treatment options available to patients with U-LMS compared with those for patients with other malignant tumors. In order to glean insight into the pathobiology of U-LMS, scientists are now using mouse models whose genomes have been specifically tailored to carry gene deletions, gene amplifications, and point mutations commonly observed in human soft tissue sarcomas. The use of these model organisms has been successful in increasing our knowledge and understanding of how alterations in relevant oncogenic, tumor suppressive, and signaling pathways directly impact sarcomagenesis. It is the aim of many in the biological community that the use of these genetically modified mouse models will serve as powerful in vivo tools to further our understanding of sarcomagenesis and potentially identify novel biomarkers and develop therapeutic strategies.